ЛЕЧЕНИЕ БОЛЬНЫХ С ЯЗВЕННОЙ БОЛЕЗНЬЮ ЖЕЛУДКАПРЕПАРАТОМ ДЕ-НОЛ В УСЛОВИЯХ ПОЛИКЛИНИКИ («Наука и здравоохранение», 2026)
ЛЕЧЕНИЕ БОЛЬНЫХ С ЯЗВЕННОЙ БОЛЕЗНЬЮ ЖЕЛУДКАПРЕПАРАТОМ ДЕ-НОЛ В УСЛОВИЯХ ПОЛИКЛИНИКИ